Possibility of Increasing Yield Potential of Rice By Reducing Panicle Height in the Canopy. II. Canopy Photosynthesis and Yield of Isogenic Lines - Setter, T.L.; Conocono, EA; Egdane, JA (Commonwealth Scientific and Industrial Research Organisation, 1996)
Reduced panicle height in a rice crop canopy may have beneficial effects of increasing yield potential through reduced shading of leaves leading to greater canopy photosynthesis. Effects of different panicle height in the canopy were evaluated in glasshouse and field experiments using isogenic lines with elongated upper internodes (EUI lines) from two cultivars. Isogenic lines of IR36 and IR50 with elongated upper internodes (IR36EUI and IR50EUI) had panicle heights at the top of the canopy of 96-100% of canopy height, while lines with low panicle heights had panicles which were 74 and 82% of canopy height respectively. Lines with low panicle height had about 10% more of the total leaf area index (LAI) above panicles and this resulted in up to 35% greater light interception by leaves above panicles relative to high panicle height plants. At 5 days before flowering IR36 and IR36EUI had equal canopy photosynthesis, while at flowering, lines had equal shoot nitrogen percentage and LAI. At maturity spikelets per mainstem were not significantly different. At 0, 7, 14 and 21 days after flowering (DAF), IR36, with low panicle height, had 10-30% greater canopy photosynthesis than IR36EUI; greater canopy photosynthesis was observed for IR50 relative to IR50EUI. These beneficial effects of low panicle height on canopy photosynthesis occurred even though the maximum single leaf photosynthesis and respiration rates were similar in both isogenic lines during grain filling. In the field and in a glasshouse experiment where plants were arranged into canopies, IR36, with low panicle heights had 15-40% greater yields than the isogenic line IR36EUI with high panicle heights; greater yields also occurred for IR50 than IR50EUI.